Subcutaneous continuous insulin infusion and control of blood glucose concentration in diabetics in third trimester of pregnancy. Issue 6222 (26th April 1980) - Potter, J M; Reckless, J P; Cullen, D R
Abstract : The effect of subcutaneous continuous insulin infusion on the control of blood glucose concentrations was assessed in eight pregnant diabetics in the third trimester. Twenty-four-hour glucose profiles were obtained after strict inpatient control on conventional insulin regimens and after the start of the continuous infusion, which was maintained for 5-55 days. Mean 24-hour glucose concentrations (6.2 mmol/l on conventional regimen, 5.9 mmol/l on continuous infusion; 111.6 and 106.2 mg/100 ml respectively) and mean fasting concentrations (5.3 v 6.2 mmol/l; 95.4 v 111.6 mg/100 ml) were not significantly changed by continuous infusion. Diurnal variations in glucose concentration tended to be smaller on continuous infusion: standard deviation from mean 24-hour glucose concentration was reduced from 2.5 to 2.0 mmol/l (from 45 to 36 mg/100 ml), maximum excursion from 8.4 to 7.4 mmol/l (151.2 to 133.2 mg/100 ml), and M value from 16 to 14. Subcutaneous continuous insulin infusion may be useful in limiting diurnal variations of blood glucose concentrations and warrants further investigation since such an action may be beneficial in the management of pregnant diabetics, in whom the best possible control of blood glucose concentrations is sought for the good of the fetus.